Perencanaan Perawatan Mesin Injection Molding Dengan Menggunakan Metode Realibility Centered Maintenance PT. Bolde Makmur Indonedia - Iqbal Maulana; Didik Aribowo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The instability of the economy and increasingly sharp competition in the industry requires a company to further enhance the efficiency of its operations. Treatment method that has been used is still corrective maintenance where engine maintenance activities undertaken to improve and enhance the condition of the engine so as to achieve the standards set at the level tersebut.Besarnya machine downtime which reaches up to 40% each month. Due to the growing number of downtime that occurs it will be increasingly detrimental to the productivity of a company. In this study used methods Realibility Centered Maintenance abbreviated to (RCM), which is to determine the optimal engine maintenance activities for the company. Reliability Centered Maintenance (RCM) is an approach that combines maintenance practices and strategies of preventive maintenance (PM) and corrective maintenance (cm) to maximize the life (life time) and the function of assets / systems / equipment at a minimal cost. Subjects studied machine is the machine Injection Molding, where the focus of engine components that will be examined as many as six parts: Barrel, Piston Injection, Toggle Clamping, Nozzle, Hydro Motor, Hopper. As for the category based on time (TD), the treatment provided in the form of component replacement schedule. Category finding damage (FF) recommended replacement components if the level of damage exceeds tolerable limits. Failure of components that include safety problem 13:33%, Outage System 80.00%, 6.67% Economic System. Of the total minimum downtime obtained Screw interval of 30 days, the crosshead link 11 days, Seal 13-day, 12-day screening. Downtime Screw impairment 37.21%, 41.15% crosshead link, Seal 24.56%, and 29.32% Screening